2013
DOI: 10.2174/18715273113129990062
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Isocitrate Dehydrogenase Following Acute Ischemic Injury as a Means to Improve Cellular Energetic Status in Neuroadaptation

Abstract: The isocitrate dehydrogenase (IDH) enzymes were initially identified as essential components of the Krebs cycle. IDH mutations were thought to be incompatible with cell survival. However, 90% of glioblastomas were recently shown to be associated with somatic mutations in these enzymes, indicating a possible role for IDH in promoting cellular survival in hypoxic environments. Our proteomic analysis of rats given 10 minutes of middle cerebral artery occlusion to induce transient ischemia demonstrates a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…The observation of less contrast enhancement in IDH ‐mutant tumors is believed to be driven primarily by the integrity of the blood‐brain barrier, which is more intact than in patients with IDH wild‐type gliomas. This is supported by report of hypoperfusion in IDH ‐mutant gliomas . Decreased permeability of the blood‐brain barrier may be related to the inhibition of angiogenesis in IDH ‐mutant glioma …”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The observation of less contrast enhancement in IDH ‐mutant tumors is believed to be driven primarily by the integrity of the blood‐brain barrier, which is more intact than in patients with IDH wild‐type gliomas. This is supported by report of hypoperfusion in IDH ‐mutant gliomas . Decreased permeability of the blood‐brain barrier may be related to the inhibition of angiogenesis in IDH ‐mutant glioma …”
Section: Introductionsupporting
confidence: 73%
“…This is supported by report of hypoperfusion in IDHmutant gliomas. 49 Decreased permeability of the bloodbrain barrier may be related to the inhibition of angiogenesis in IDH-mutant glioma. 50,51 The most striking clinical correlation that reinforced the theory that IDH-mutant gliomas behave differently is the finding that patients with an IDH-mutant glioma live longer than patients with IDH wild-type glioma.…”
Section: Clinical Features Of Idh-mutant Gliomamentioning
confidence: 99%
“…Moreover, in the model, we observed an increased flux in antioxidant enzymes and key enzymes in glycolysis (Table 4 ). In this aspect, many studies have shown that these enzymes can be part of a machinery for cultured astrocytes to adapt to an ischemic environment, suggesting that the overexpression of antioxidant enzymes may be an important protective mechanism that prevents brain injury (Sonnewald et al, 1994 ; Niitsu et al, 1999 ; Grelli et al, 2013 ). Overall, the in silico predictions of our model, are similar to those experimentally reported in ischemic astrocytes, suggesting the predictive value of the present model.…”
Section: Resultsmentioning
confidence: 99%
“…The reported role of quercetin on autophagy-mediated cell survival, in order to counteract brain injury-induced apoptosis, suggested us to comment the reported data by Fawad-Ali Shah et al as we retrieved further insights on the role of quercetin in MCAO. We realized that some of the upregulated proteins reported by the authors are also involved in the modulation of autophagy [17][18][19][20].…”
mentioning
confidence: 78%